(untitled) - Imhoff, Claudia (Indianapolis, 2003)
A cutting-edge response to Ralph Kimball's challenge to the data warehouse community that answers some tough questions about the effectiveness of the relational approach to data warehousing. Written by one of the best-known exponents of the Bill Inmon approach to data warehousing. Addresses head-on the tough issues raised by Kimball and explains how to choose the best modeling technique for solving common data warehouse design problems. Weighs the pros and cons of relational vs. dimensional modeling techniques. Focuses on tough modeling problems, including creating and maintaining keys and modeling calendars, hierarchies, transactions, and data quality
Keywords: Data warehousing,Kho dữ liệu